2015
DOI: 10.1159/000438979
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proendothelin-1 as an Early Marker of Bronchopulmonary Dysplasia

Abstract: Background: Bronchopulmonary dysplasia (BPD) is a common complication in preterm infants. Clinical prediction of BPD at an early stage in life is difficult. Plasma proendothelin-1 (CT-proET-1) is a lung injury biomarker in pulmonary hypertension and respiratory distress. Objective: To assess the prognostic ability of CT-proET-1 in BPD. Methods: In 227 prospectively enrolled preterm infants born at <32 weeks gestational age (GA), plasma CT-proET-1 was measured at birth, day of life (DOL) 2, 3, 6 and 28, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The predictive value of CT-proET1 for BPD development was highest on DOL 6. In contrast to our current study, Baumann et al showed a persistent association of CT-proET1 with BPD/death even after correction for clinical factors [ 16 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The predictive value of CT-proET1 for BPD development was highest on DOL 6. In contrast to our current study, Baumann et al showed a persistent association of CT-proET1 with BPD/death even after correction for clinical factors [ 16 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In multivariable logistic regression analysis of our results with birth weight, RIMP, TAPSE, MR-proANP and CT-proET1 in the equation, only birth weight and RIMP remained independent predictors of BPD/death. In a previous study of our group including 227 preterm infants, plasma CT-proET1 was measured at birth, DOL 2, 3, 6, and 28 [ 16 ]. The predictive value of CT-proET1 for BPD development was highest on DOL 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, they found that the predictive ability of plasma proendothelin was moderate at days 2 and 3 of life but was excellent at day 6 of life; the area under ROC curve was 0.918 [21].…”
Section: Discussionmentioning
confidence: 98%
“…6b). Baumann et al [39] found a significant difference in a precursor of ET-1 in BPD-affected children until 28 days of age only. However, this difference vanished at 36 weeks postmenstrual age.…”
Section: Discussionmentioning
confidence: 99%